Analisis Faktor yang Menjadi Alasan Nasabah Memilih Deposito Mudharabah di BPRS XYZ - Julia Noermawati Eka Satyarini (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
This research aims to explain what factors into the reasons customers choose deposit in BPRS XYZ and the sample used is that customers save their money in the form of deposit. There were 33 questionnaires from respondents who may be samples of research and then use Chocran Q Test method to analyze the data. Based on the result of the research can be conclude that customers who deposit fund in the form of deposits have different reason factor. It this can be seen from the result of acalculation that shows Q countdown (36.00) > Q table (12.592) which means refused table Ho. And the results can also be seen that the most dominant factor is the factors owned by customers and security service with the same percentage (93.94).